Electoral system, confidence and no-confidence vote: three examples of constitutional flexibility and doctrinal arbitrism - Alba Navarro, Manuel (Journal of the Basque Parliament, 2020)
The changes that happened in spanish political system from 2015 did affect to the parties system, which has deeply changed. The versatility of 1978 Constitution (electoral system included) has been proved in order to allow this change and, at the same time, been capable to face political instability. Nevertheless these changes have shooted up reform proposals made by doctrine. Inadvisables most of them.